Melatonin prevents oxidative stress and inhibits reactive gliosis induced by hyperhomocysteinemia in rats - Baydas, G; Ozer, M; Yasar, A; Koz, ST; Tuzcu, M (Pleiades Publishing Ltd, 2006)
Homocysteine (Hcy), an independent risk factor for atherosclerosis, undergoes auto-oxidation and generates reactive oxygen species, which are thought to be main cause of Hcy neurotoxicity. However, the mechanisms leading to neurodegenerative disorders are poorly understood because studies that have investigated the potential neurotoxicity of hyperhomocysteinemia in vivo are scarce. The purpose of this study was to test whether daily administration of methionine, which induces hyperhomocysteinemia, causes glial hyperactivity, and also to investigate the protective effects of melatonin on the brain tissue against oxidative stress of Hey in rats. There was a significant development of oxidative stress as indicated by an increase in malondialdehyde + 4-hydroxyalkenals in hippocampus and cortex of hyperhomocysteinemic rats, whereas significant reduction was found in the activity of glutathione peroxidase (GSH-Px). Co-treatment with melatonin inhibited the elevation of lipid peroxidation and significantly increased GSH-Px activity in the brain regions studied. Western blot analysis revealed an increase in glial fibrillary acidic protein (GFAP) contents both in hippocampus and frontal cortex (p < 0.001) of hyperhomocysteinemic rats compared to the controls. Administration of melatonin significantly decreased GFAP contents in hippocampus and cortex (p < 0.05). S100B contents increased only in frontal cortex in hyperhomocysteinemic rats compared to the control (p < 0.01) and was inhibited by melatonin treatment (p < 0.01). The present findings show that Hey can sensitize glial cells, a mechanism which might contribute to the pathogenesis of neurodegenerative disorders, and further suggest that melatonin can be involved in protecting against the toxicity of Hey by inhibiting free radical generation and stabilizing glial cell activity.
Keywords: melatonin; glial fibrillary acidic protein; S100B protein; lipid peroxidation; glutathione peroxidase